Comparison Analysis of EVA and ROA Methods in Assessing The Financial Performance of The Company - Ita Lestari; Susanti Susanti; Ewing Yuvisa Ibrani; Mahpudin Mahpudin (Journal of Applied Business, Taxation and Economics Research, 2022)
This study aims to determine the company's financial performance by using a comparative analysis of the Economic Value Added (EVA) and Return On Assets (ROA) methods. This study employed pre-field research techniques and on-site fieldwork to conduct descriptive qualitative research. Secondary data, data gathering methods utilizing report studies and literature analyses, and data analysis methods utilizing data collection, data reduction, data presentation, and data inference techniques are all used as the data sources. To verify the accuracy of the data, the author uses three sources and three different techniques. The results showed that EVA INDF in the 2014-2016 period produced an EVA value < 0, which could be interpreted as unfavorable, ICBP, MYOR, and ROTI in the 2014-2018 period, on average, produced an EVA value > 0 which could be construed as positive. Except for ROTI in the last three years which resulted in an EVA < 0. Meanwhile, ROA INDF, ICBP, MYOR, and ROTI in 2014-2018 produced an average ROA value above the industry standard or can be said to be good. Except for INDF in 2015, 2017, and 2018, the average ROA value is below industry standards. This study concludes that EVA analysis is better because if the average value of EVA is> 0, then the company can provide added value to investors. At the same time, the ROA analysis produces an average ROA value below the industry standard.